Peat soil quality index and its determinants as influenced by land use changes in Kubu Raya District, West Kalimantan, Indonesia - ROSSIE WIEDYA NUSANTARA; ASRIPIN ASPAN; ABDUL MUJID ALHADDAD; URAY EDI SURYADI1; MAKHRAWIE MAKHRAWIE; IRMA FITRIA; JAINI FAKHRUDIN; REZEKIKASARI REZEKIKASARI (Society for Indonesian Biodiversity, 2018)
Nusantara RW, Aspan A, Alhaddad AM, Suryadi UE, Makhrawie, Fitria I, Fakhrudin J, Rezekikasari. 2018. Peat soil quality index and its determinants as influenced by land use changes in Kubu Raya District, West Kalimantan, Indonesia. Biodiversitas 19: 585-590. Tropical peatland is continuously damaged in large area in Indonesia, caused by deep and wide drains which change the ecosystem. This research was conducted to evaluate the soil quality index (SQI) based on peatland use. The research was conducted in Kubu Raya District, West Kalimantan Province, in secondary peat forest, shrubland, oil palm plantation and corn field. The variables observed in this research were subsidence, water-table level, depth of peat, bulk density, water content, porosity, organic carbon, total nitrogen, total potassium, cation exchange capacity, base saturation, ash content, available phosphorus, and exchangeable calcium, magnesium, sodium, C/N ratio and soil acidity. The results showed that SQI in secondary peat forest, shrubland, corn field and palm oil plantation were 0.40, 0.37, 0.37 and 0.37 respectively. The stepwise regression analyses showed that the variables influencing SQI were the depth of peat, water-table level, and ash content. Secondary forest had the highest level (0.74) for the depth of peat with 509 cm depth while the other sites had average level (0.41-0.43) with 108.4 cm-115.5 cm mean depth. SQI of peatland increased with the increasing depth of peat and ash content. The differences showed that land use change of peatland, from forest to plantation area would decrease its SQI.